Beyond emergency relief: What will it take to ensure a resilient recovery for agriculture and the rural economy of Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
The recent history of rural economic transformation in Myanmar and the effects of COVID-19 and the military coup in February 2021 provide important lessons for the design and implementation of plans to help the country recover from these scourges. The impoverishment of farming communities in Myanmar during decades of socialist military rule, beginning in the 1960s until the turn of the century, led to an outflux of migrants to neighboring countries. As the country opened up to foreign investment through economic reforms initiated in 2011, rural wages surged and farm mechanization services expanded rapidly. Together with increased remittance flows from migrants, higher rural household incomes drove growth in a wide range of non-farm service enterprises. Nevertheless, agricultural growth was low and most crop subsectors stagnated due to underlying and unresolved structural constraints such as poor infrastructure and inequality in land access. As in many other countries in Asia, border closures and lockdowns instituted to prevent the spread of COVID-19 in early 2020 resulted in widespread employment and income losses. The Myanmar government pro-actively sought to mitigate the impacts through expanded credit to farmers and businesses. By the end of 2020, Myanmar was beginning to recover from the economic stresses of COVID-19. However, the February 2021 military coup resulted in a far more severe economic downturn than COVID-19 due to the collapse of the financial system, the massive resignations by public sector employees, and the prolonged movement restrictions. Coup-induced state failure greatly magnified the health and economic consequences of COVID-19 in terms of poverty, food insecurity, and stalled economic transformation. This paper uses a combination of macro, meso, and micro-level analyses to measure the impacts of COVID-19 and state failure on rural economic transformation through the lens of the agri-food system, and to draw lessons for policies to support broad-based and resilient economic recovery.